2003
DOI: 10.1074/jbc.m211981200
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Human NAD(P)H:Quinone Oxidoreductase 1 (NQO1) with the Tumor Suppressor Protein p53 in Cells and Cell-free Systems

Abstract: NAD(P)H:quinone oxidoreductase 1 (NQO1) has been proposed to stabilize p53 via a redox mechanism involving oxidation of NAD(P)H as a consequence of the catalytic activity of NQO1. We report that treatment of HCT-116 human colon carcinoma cells with the NQO1 inhibitor ES936 had no effect on the levels of p53 protein. ES936 is a mechanism-based inhibitor of NQO1 that irreversibly blocks the catalytic function of the enzyme. This suggests that a redox mechanism involving NQO1-mediated NAD(P)H oxidation is not res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
92
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(96 citation statements)
references
References 48 publications
(50 reference statements)
3
92
1
Order By: Relevance
“…Dicoumarol has been reported to have various functions through inhibition of NQO1, including accumulation Dicoumarol-mediated enhancement of CDDP cytotxicity J Watanabe et al of intracellular reactive oxygen species (ROS) (Lewis et al, 2004) or abrogation of p53 protein (Asher et al, 2001;Anwar et al, 2003). Ubiquitous expression of NQO1 was confirmed in the examined cell lines, and these cells also presented the almost similar sensitivity to dicoumarol.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Dicoumarol has been reported to have various functions through inhibition of NQO1, including accumulation Dicoumarol-mediated enhancement of CDDP cytotxicity J Watanabe et al of intracellular reactive oxygen species (ROS) (Lewis et al, 2004) or abrogation of p53 protein (Asher et al, 2001;Anwar et al, 2003). Ubiquitous expression of NQO1 was confirmed in the examined cell lines, and these cells also presented the almost similar sensitivity to dicoumarol.…”
Section: Discussionmentioning
confidence: 66%
“…3-3 0 -Methylene-bis [4-hydroxycoumarin] (dicoumarol) was characterized as an enzymatic inhibitor of NQO1 and was shown to inhibit proliferation of pancreatic cancer cells through an accumulation of oxidative stress (Madari et al, 2003;Lewis et al, 2004). In addition, dicoumarol induced p53 degradation through NQO1 inhibition and modulated p53-mediated apoptosis in g-irradiated normal thymocyte (Asher et al, 2001;Anwar et al, 2003). In the present study, to assess the possibility of NQO1 as a modulator for anticancer agents, we investigated the cytotoxic effects of dicoumarol in combination with CDDP, using cell lines derived from bladder and prostate cancers.…”
Section: Introductionmentioning
confidence: 99%
“…This twoelectron reduction prevents the formation of semiquinone free radicals and reactive oxygen species (ROS), thus protecting cells against oxidative stress, cytotoxicity, and mutagenicity (Tsvetkov et al, 2010). Furthermore, both in vivo and in vitro studies have confirmed that NQO1 regulates the stability of the tumor suppressor p53 (Asher et al, 2002;Anwar et al, 2003). NQO1-deficient mice show reduced p53 induction and apoptosis, increased sensitivity to chemically induced tumors (Long et al, 2000;Iskander et al, 2005).…”
Section: Research Articlementioning
confidence: 99%
“…Microarray identification of candidate p63 target genes containing REs conforming to the p63 DBS Primary human mammary epithelial cells (HMECs) normally express the p63 isoform DNp63a, have a functional p53 pathway (Anwar et al, 2003) and therefore are a suitable model system to distinguish shared and distinct targets genes of the p53 family. To this end, we transduced HMECs with adenoviruses expressing p53, TAp63g or GFP, and performed comparative global gene expression analysis using Affymetrix microarray technology.…”
Section: P63 Binds a Dna Motif With Unique Characteristicsmentioning
confidence: 99%